2021
DOI: 10.7324/japs.2021.110415
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiod influenced the growth and antioxidative responses of Chlorella vulgaris, Isochrysis galbana, and Tetraselmis chuii

Abstract: Microalgae are rich in natural antioxidants, with occurrence and quality depending primarily on the species of microalgae and the conditions of cultivation. Light and photoperiod affect microalgae accumulation of antioxidants. This study examined the growth, biomass, and antioxidant responses of microalgae Chlorella vulgaris (UMT-M1), Isochrysis galbana (CB), and Tetraselmis chuii (CT) grown in 30 ppt F/2-enriched seawater and exposed to 12:12 and 24:0 hours light/dark cycles at 24°C ± 2°C. Overall cell densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 50 publications
0
2
0
5
Order By: Relevance
“…growth and antioxidant response against reactive oxygen species (ROS). Shafiqa et al (2021) studied the photoperiodism effect on the growth and antioxidant activities in T. chuii CT, C. vulgaris UMT-M1, and I. galbana by providing light and dark conditions in 12 h:12 h and 24 h:0 h. The result showed that continuous light supply (24 h:0 h) significantly increased the biomass, chl-a and b, ascorbic acid, and carotenoids accumulation in all the microalgae. Moreover, photon flux also has an impact on the growth and wastewater treatment by microalgae.…”
Section: Effects Of Physiological Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…growth and antioxidant response against reactive oxygen species (ROS). Shafiqa et al (2021) studied the photoperiodism effect on the growth and antioxidant activities in T. chuii CT, C. vulgaris UMT-M1, and I. galbana by providing light and dark conditions in 12 h:12 h and 24 h:0 h. The result showed that continuous light supply (24 h:0 h) significantly increased the biomass, chl-a and b, ascorbic acid, and carotenoids accumulation in all the microalgae. Moreover, photon flux also has an impact on the growth and wastewater treatment by microalgae.…”
Section: Effects Of Physiological Conditionsmentioning
confidence: 99%
“…The study showed that in low light intensity (33 μmolm −2 s −1 ) β-carotene accumulation increased up to 3-fold whereas, in high light intensity (170 and 280 μmolm −2 s −1 ) lutein accumulation increased. Recent studies have suggested that light plays an important role in the synthesis of antioxidant biomolecules which has a role in conquering the development of ROS in microalgae species into the chloroplast, peroxisomes, mitochondria, and apoplasts (Shafiqa et al 2021). Photoperiodism also has an important role in Tetraselmis sp.…”
Section: Effects Of Physiological Conditionsmentioning
confidence: 99%
“…Harapannya adalah agar dapat memicu produksi senyawa antioksidan. Menurut Yusof et al (2021), mikroalga kaya akan antioksidan alami, namun jenis senyawa, kuantitas, dan kualitas metabolit yang disintesis tergantung spesies miroalga dan kondisi kulturnya. Selama fotosintesis, peningkatan intensitas cahaya PAR dapat digunakan untuk menginduksi produksi banyak metabolit sekunder pada tanaman.…”
Section: Hasil Dan Pembahasanunclassified
“…Senyawa fungsional yang terdapat dalam biomassa mikroalga telah diketahui merupakan sumber antioksidan alami, sehingga dapat dimanfaatkan sebagai peredam radikal bebas dalam tubuh. Antioksidan alami yang dihasilkan mikroalga termasuk pigmen, fenolik, dan tokoferol (Safafar et al, 2015;Canelli et al, 2022;Yusof et al, 2021). Chlorella vulgaris adalah contoh mikroalga yang telah dimanfaatkan sebagai suplemen makanan dan berperan sebagai mediator yang efektif dalam menangkal radikal bebas.…”
unclassified
“…Con respecto al mejoramiento de la eficiencia de la cinética de crecimiento de la microalga en respuesta a los cambios del fotoperiodo, Sirisuk et al [12] determinaron que el crecimiento celular bajo diferentes WL varía de acuerdo con el fotoperiodo utilizado. La luz continua (24h) aplicada a los cultivos tiene un efecto directo positivo en su capacidad para aumentar la biomasa [15], sin embargo, Sirisuk et al [12] y Zhong et al [13], probaron otros fotoperiodos similares a las condiciones de luz natural y determinaron que bajo un régimen de irradiación de 16h:8h (L/O), la densidad celular aumenta, esto permite mejorar la eficiencia de producción al cultivar las microalgas con iguales o mejores resultados de crecimiento y a un menor costo energético. Yoshioka et al [14], cultivaron Isochrysis galbana, hicieron modificaciones en la WL y el fotoperiodo y observaron que estos cambios tienen un efecto positivo en la cinética de crecimiento, pues bajo condiciones de luz azul intermitente, hubo aumento de la densidad celular, comparada con el tratamiento control de luz blanca continua, reportaron una densidad celular de 3.5±0.6×10 5 células mL −1 y 1.9±0.3×10 5 cel/ ml −1 respectivamente.…”
Section: Introductionunclassified